Pengujian dosis larutan air garam (NaCl/Natrium Cloride) terhadap daya tetas telur itik pedaging hibrida super - Rosidi Azis Azis (Jurnal Ilmu-Ilmu Peternakan, 2018)
Duck egg has a thicker eggshell than chicken. It is become one of the factors of embryonic death. Salt is a compound known to have corrosive properties. The purpose of this study is to test the effectiveness of salt spraying with different dosage of hatchability of super hybrid duck eggs. The experimental design used was experimental with Completely Randomized Design (CRD) with 4 treatments. Treatment R0 spraying using water, R1 salt water spraying with dosage 10gr / L water, R2 salt water spraying with dosage 20gr / L water, R3 salt water spraying with dosage 30gr / L water. The results of different ANOVA will be tested further using Duncan with 5% test level. The results of this study were salt spraying gave a real effect (P <0.05) on fertility, and a very significant effect (P <0.01) at hatching time, but did not have a significant effect (P> 0.05) on mortality and hatchability. The conclusion of this research was salt water spraying on duck eggs could increase fertility and shorten the age of hatching.